PENGARUH KOMPETENSI GURU DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi pada Pendidik Pendidikan Anak Usia Dini di Kecamatan Pati) - Rusminingsih Rusminingsih; Euis Soliha (Universitas Peradaban, 2014)
Teachers as educators is an educational leader, which is crucial in the learning process. Less than optimal performance of early childhood educators in District Pati, is a problem that must be addressed. Early childhood educator competencies and job characteristics in teaching should be improved as well as a strong commitment to be created and to use order to obtain higher performance. This study aims to determine the effect of teacher competence and job characteristics on performance by mediating organizational commitment (studies in early childhood education teachers in the district Pati).The research was conducted on educators of early childhood education in the District of Pati as many 140 people. Sample taking the entire population for the research sample. Data analysis use multiple regression analysis.Results reveal that the competence effect on organizational commitment. Positive effect on the employment characteristics of organizational commitment. Competence has a positive effect on the performance of early childhood educators. Job characteristics affect employee performance early childhood educators. Organizational commitment has a positive effect on the performance of early childhood educators. Organizational commitment did not mediate the effect of competence on the performance of early childhood educators. Organizational commitment did not mediate the effect of job characteristics on the performance of early childhood educators.